Adherence to standard precautions by nursing professionals in Brazil during the COVID-19 pandemic: a cross-sectional study - Cordeiro, Daniella Corrêa; Cordeiro, Jéssica Fernanda Corrêa; Gomes, Ludmila Albano Felix; Cruz, Tatiana Ares da; Valim, Marilia Duarte; Andrade, Denise de; Santos, André Pereira dos (Revista Prevenção de Infecção e Saúde, 2023)
Introduction: COVID-19 is an infectious disease caused by the SARS-CoV-2, which has a very high degree of contamination and confers patients and health professionals at risk. Thus, one wonders about the rate of adherence to standard precautions by nursing professionals from different contexts in the country. Aim: To identify adherence to Standard Precautions (SP) by nursing professionals who provided care during the COVID-19 pandemic and to verify the association between adherence to SP and sociodemographic and work characteristics. Outlining: Cross-sectional observational study, carried out with 493 nursing professionals working in nursing care in the five regions of Brazil. Data collection was carried out through Google Forms®, using social networks, the recruitment of participants took place between November 2020 and December 2021. Descriptive analysis was performed and the results presented by absolute and relative frequency. Pearson’s chi-square test (X²) was used to verify the association between adherence to SP (≥ 75 points) and sociodemographic and work variables. Results: In the total sample, 353 (71.6%) professionals adhered and 140 (28.3%) did not. There was an association between age group (40 to 49 years) with adherence to SP in the total sample. Implications: Nursing professionals showed a deficit in adherence to SP, with younger people less likely to adhere, bringing great impacts to the health of professionals.